Benchmarking collateral of triple-a rated securities (2020)
This paper presents a simple method to estimate the collateral associated with a Aaa tranche. The method is similar to historical simulation in the sense that there are no specific distributional assumptions, and the data fully determine the characteristics of the distribution. Both the transparency and simplicity of our method provide a valuable benchmark to existent tail of the distribution modelling. As a benchmark, our method also serves to validate collateral estimates for Aaa-rated securities as well as to validate capitalization models of financial institutions.